Teacher-student collaborative assessment and content-based instruction:A case study of english writing at a Chinese University - Li Qiu; Suyansah Swanto; Noraini binti Said; Wardatul Akmam Din; Chunguang Li (Journal of Higher Education Theory and Practice, 2024)
This study delves into the impact of corrective feedback within a Teacher-Student Collaborative Assessment (TSCA) and Content-Based Instruction (CBI) framework on EFL (English as Foreign Language) students' English writing and grammar learning. A ten-week experiment with one hundred participants explores this question. Divided into three groups, one receives direct corrective feedback, another navigates indirect feedback, and a control group receives none. Evaluating writing performances across these groups, the study aims to assess the combined efficacy of TSCA and CBI in promoting English grammar learning. Preliminary findings suggest that corrective feedback within the TSCA and CBI framework significantly enhances grammar accuracy. This study proposes an innovative methodology, highlighting comprehensive corrective feedback as a transformative catalyst for grammar development. It introduces a unique module for EFL students, fostering proficiency in English grammar and potentially transcending limitations associated with TSCA alone. This approach paves the way for a fresh paradigm within EFL grammar learning.